Technical and Economic Evaluation of Electricity Generation and Storage Using Renewable Energy Sources on Socotra Island, Yemen - Serag, Saif; Echchelh, Adil (Iraqi Journal of Science, 2023)
Renewable energy sources are a promising hope for avoiding many environmental and economic problems such as the problems of climate change and environmental pollution resulting from fossil fuels combustion, in addition to the problems of oil derivatives high prices and their absence in many countries, which in turn affected the rise in electricity prices. Yemen is considered one of the countries most affected by electricity prices rise due to lack of oil derivatives as a result of the ongoing wars in Yemen. This paper presents a technical and economic study of renewable energy sources for producing and storing electricity. It gives a clear scientific and economic vision for implementation of these projects in one of the Yemeni islands, Socotra. This study has proven the high efficiency of energy sources in this region, which encourages their use to produce electricity to cover the region needs at low prices compared to the current prices of electricity in Yemen., where the cost of electricity from renewable energy sources ranges between 0.073 to 0.25 $ / kWh. The study also provides an assessment of the expected decline in electricity prices until 2030. It should be noted that this study can be applied to many coastal cities and other islands in Yemen at a cost close to this cost.